Harmonization of Islamic Law, Customary Law, and National Law in Safeguarding the Rights of Indigenous Peoples - Muhammadong (Legal Frontier, 2025)
This study explores the harmonization of Islamic law, customary law (adat), and national law in the context of protecting the rights of indigenous peoples in Indonesia. As a country with legal pluralism, Indonesia accommodates multiple legal systems that coexist and often intersect. Customary law, deeply rooted in indigenous communities, plays a vital role in regulating social life and managing communal resources. However, its recognition and implementation within the national legal framework remain inconsistent. Islamic law, as one of the moral and legal foundations embraced by the majority of the population, offers universal principles of justice, equity, and protection of rights, including those of marginalized groups. This research analyzes how Islamic legal values can serve as a bridge between state law and adat law to ensure comprehensive protection for indigenous communities. Using a normative-juridical approach, the study reviews legislation, judicial decisions, and scholarly interpretations to assess the compatibility and potential conflicts among these legal systems. The findings indicate that while overlaps exist particularly in principles of communal ownership, justice, and mutual respect practical harmonization is often hindered by regulatory ambiguities and lack of political will. The study recommends the formulation of an integrated legal framework that respects the autonomy of indigenous law, aligns with Islamic principles of maslahah (public interest), and complies with constitutional protections. Such harmonization not only strengthens legal certainty but also ensures that indigenous peoples can fully exercise their rights without discrimination or marginalization. This research contributes to the discourse on legal pluralism and social justice in multicultural societies